Laboratory characterization of PM emissions from combustion of wildland biomass fuels. Issue 17 (9th September 2013) - Hosseini, S.; Urbanski, S. P.; Dixit, P.; Qi, L.; Burling, I. R.; Yokelson, R. J.; Johnson, T. J.; Shrivastava, M.; Jung, H. S.; Weise, D. R.; Miller, J. W.; Cocker, D. R.
Abstract : [1] Particle emissions from open burning of southwestern (SW) and southeastern (SE) U.S. fuel types during 77 controlled laboratory burns are presented. The fuels include SW vegetation types: ceanothus, chamise/scrub oak, coastal sage scrub, California sagebrush, manzanita, maritime chaparral, masticated mesquite, oak savanna, and oak woodland, as well as SE vegetation types: 1 year, 2 year rough, pocosin, chipped understory, understory hardwood, and pine litter. The SW fuels burned at higher modified combustion efficiency (MCE) than the SE fuels resulting in lower particulate matter mass emission factor. Particle mass distributions for six fuels and particle number emission for all fuels are reported. Excellent mass closure (slope = 1.00, r 2  = 0.94) between ions, metals, and carbon with total weight was obtained. Organic carbon emission factors inversely correlated ( R 2  = 0.72) with average MCE, while elemental carbon (EC) had little correlation with average MCE ( R 2  = 0.10). The EC/total carbon ratio sharply increased with MCE for MCEs exceeding 0.94. The average levoglucosan and total polycyclic aromatic hydrocarbon (PAH) emissions factors ranged from 25 to 1272 mg/kg fuel and 1.8 to 11.3 mg/kg fuel, respectively. No correlation between average MCE and emissions of PAHs/levoglucosan was found. Additionally, PAH diagnostic ratios were observed to be poor indicators of biomass burning. Large fuel type and regional dependency were observed in the emission rates of ammonium, nitrate, chloride, sodium, and potassium. Key Points: Chem. and phys. charact. of emissions from Southewest and Southeast US veg. Comprehensive analysis of PAH/levoglucosan emissions from 77 burns Investigating effect of MCE and vegetation type on emissions